Antidepressant Use and Suicide Rates in Adults Aged 75 and Above: A Swedish Nationwide Cohort Study - Hedna, Khedidja; Fastbom, Johan; Erlangsen, Annette; Waern, Margda (Frontiers in Public Health, 2021)
Background The treatment of depression is a main strategy for suicide prevention in older adults. We aimed to calculate suicide rates by antidepressant prescription patterns in persons aged ≥75 years. A further aim was to estimate the contribution of antidepressants to the change in suicide rates over time. Methods Swedish residents aged ≥75 years (N=1 401 349) were followed between 2007 and 2014 in a national register-based retrospective cohort study. Biannual suicide rates were calculated for those with selective serotonin reuptake inhibitor (SSRI) single use, mirtazapine single use, single use of other antidepressants and use of ≥2 antidepressants. The contribution of antidepressants to the change in biannual suicide rates was analysed by decomposition analysis. Results There were 1277 suicides. About one third of these were on an antidepressant during their last 3 months of life. In the total cohort, the average biannual suicide rate in non-users of antidepressants was 13 per 100 000 person-years. The corresponding figure in users of antidepressants was 34 per 100 000 person-years. These rates were 25, 42 and 65 per 100 000 person-years in users of SSRI, mirtazapine and ≥ 2 antidepressants, respectively. In the total cohort, antidepressant users contributed by 26% to the estimated increase of 7 per 100 000 in biannual suicide rates. In men, biannual suicide rates increased by 11 suicides per 100 000 over the study period; antidepressant users contributed by 25% of the change. In women, those on antidepressant therapy accounted for 29% of the estimated increase of 4.4 per 100 000. Conclusion Only one third of the oldest Swedish population who died by suicide filled an antidepressant prescription in their last 3 months of life. Higher suicide rates were observed in mirtazapine users compared to those on SSRIs. Users of antidepressants accounted for only one quarter of the increase in the suicide rate. The identification and treatment of suicidal older adults remains an area for prevention efforts.